Jesus, The Prophet, The Messiah, And The Host: An Interpretation Of Luke 24:13-35 - Yahya, Pancha W. (Sekolah Tinggi Teologi SAAT, 2018)
The story of Jesus’ encounter with two disciples on the journey to Emmaus is a unique story, among which is the story contains the question: what really made two disciples not recognize Jesus?, and why after inviting Jesus to their home, the identity of Jesus was recognized. Many solutions have been offered to answer these complicated problems, but it seems that the answers proffered are less than convincing. According to the author, the Emmaus story must be seen from the entire book of Luke and Acts because in this episode there are important themes scattered throughout Luke’s two writings. The two disciples are representatives of Jews who cannot understand that the Messiah must suffer, be crucified, and be resurrected. What made them recognize Jesus again was when Jesus entertained them to eat? It was because it reminded them of a similar event before Jesus’ death and at the same time referred to the role of Yahweh as the host of His OT people and the hope of an eschatological meal. In the end, the theme of this dining table fellowship became important in the Acts of the Apostles in relation to Jewish and Gentile relations within the early church. Keywords: Emmaus, Motif of Ignorance, Table Fellowship, Rejected Messiah Cerita perjumpaan Yesus dengan dua murid dalam perjalanan ke Emaus merupakan kisah yang unik, di antaranya adalah kisah ini mengandung pertanyaan: apa yang sesungguhnya membuat dua murid tidak mengenali Yesus dan mengapa setelah mengundang Yesus ke rumah mereka, identitas Yesus tersingkapkan. Banyak solusi telah coba untuk ditawarkan untuk menjawab persoalan pelik ini, namun sepertinya jawaban-jawaban itu kurang meyakinkan. Menurut penulis, kisah Emaus harus dilihat dari keseluruhan kitab Lukas dan Kisah Para Rasul karena di dalam episode ini termaktub tema-tema penting yang tersebar di sepanjang dua tulisan Lukas itu. Dua murid merupakan perwakilan orang Yahudi yang tidak dapat memahami bahwa Mesias harus menderita, disalibkan, dan dibangkitkan. Yang membuat mereka mengenal kembali Yesus adalah ketika Yesus menjamu mereka makan, karena itu mengingatkan peristiwa yang serupa sebelum kematian Yesus sekaligus merujuk pada peran Yahweh sebagai penjamu umat-Nya dalam PL dan harapan akan jamuan eskatologis. Pada akhirnya, tema persekutuan meja makan ini menjadi penting dalam Kisah Para Rasul dalam kaitan dengan relasi Yahudi dan non Yahudi dalam gereja mula-mula. Kata-kata kunci: Emaus, Motif Ketidaktahuan, Persekutuan Meja Makan, Mesias yang Ditolak